Fleas (Siphonaptera) Parasitizing Peridomestic and Indigenous Mammals in Panamá and Screening of Selected Fleas for Vector-Borne Bacterial Pathogens. Issue 3 (20th November 2020) - Durden, Lance A; Bermúdez, Sergio; Vargas, Géminis A; Sanjur, Boris E; Gillen, Laura; Brown, Lisa D; Greiman, Stephen E; Eremeeva, Marina E
Abstract: In total, 341 fleas belonging to 16 species were collected from 78 host mammals belonging to 10 species in Panamá from 2010 to 2016. The cat flea, Ctenocephalides felis (Bouché) predominated on domestic dogs and was also recorded from domestic cats, the raccoon, Procyon lotor (Linnaeus) and the common opossum, Didelphis marsupialis Linnaeus. The largest number of flea species (7) was recorded from D. marsupialis and the most common flea on that host was the ctenophthalmid, Adoratopsylla intermedia copha Jordan. One Oriental rat flea, Xenopsylla cheopis (Rothschild), was collected from D. marsupialis . Native rodents were parasitized by indigenous ceratophyllid, rhopalopsyllid, and stephanocircid fleas. The Mexican deermouse, Peromyscus mexicanus (Saussure), was parasitized by six species of ceratophyllids belonging to the mostly Central American genera, Baculomeris, Jellisonia, Kohlsia and Plusaetis. The long-tailed singing mouse, Scotinomys xerampelinus (Bangs), was parasitized by Plocopsylla scotinomi Tipton and Méndez, the only species of stephanocircid flea known from Central America. Twenty-six pools of extracted flea DNA representing 5 flea species ( C. felis, Pulex echidnophagoides (Wagner), Pulex simulans Baker, A. intermedia copha, and P. scotinomi ) and 79 individual fleas were all real-time polymerase chain reaction negative for Rickettsia felis, Rickettsia typhi, and Bartonella henselae .